Indian club swinging in the early Victorian period. Issue 1 (2nd January 2017) - Heffernan, Conor
ABSTRACT: Although relatively unknown to the modern fitness enthusiast, Indian club swinging, the practice of swinging bottle shaped clubs for gymnastic exercise, was once a highly popular form of recreation and rehabilitation in Victorian England. Inspired by the centuries-old Indian practice of jori swinging, club swinging first emerged in England in the 1820s, thanks to its adoption by the British army. Although first viewed as a military training practice, club swinging was soon appropriated by England's upper-classes with an eye to gender identities. For Victorian men, Indian clubs were seen as a means of bolstering their masculine credentials through the cultivation of physical strength. Similarly for women, club swinging was presented as an innocuous method of preserving or increasing their beauty. By tracing the importation of Indian club swinging into English society, this article examines the ways in which the practice was used to both bolster and re-interpret the gender identities ascribed to Indian clubs by both physicians and lay authors.